AVALIAÇÃO DAS PROPRIEDADES FÍSICAS DO SOLO E MACROFAUNA EM UM PLANTIO DE RECUPERAÇÃO DE NASCENTE - SILVA, Thaís Tagliati; CASTILHO, Selene Cristina de Pierri; GONÇALVES, João Vitor Correa; ROSSET, Jean Sérgio; MARRA, Leandro Marciano (ANAIS DO ENIC, 2018)
-